Análisis de los sabores ancestrales del Inti Raymi en la comunidad La Calera, Cantón Cotacachi. - Ipiales Guerrero, Jocelyn Jazmín (2022)
The ancestral knowledge of the Inti Raymi are events that have been passed down for generations, as it involves the most identifying ancestral practices of each of the cultures, reflecting the preservation of their original roots such as clothing, dance, music, food and their dialects in the native language, this celebration denotes the connection with mother earth, its origins and mainly the empowerment generated during the dates of June and July. This study proposes to document the ancestral knowledge of Inti Raymi in the community of La Calera, Cotacachi, through the development of a digital magazine to disseminate and revalue their cultural identity. The methodology is based on basic research with a mixed approach, which is aligned with the analytical - synthetic and deductive - inductive research methods, of equal importance three research techniques are applied: survey, interview and observation\; we worked with a non-probabilistic sample of convenience, which was applied to 100 people belonging to the canton Cotacachi. In the results, information was collected about the Inti Raymi in which it is known that this celebration is derived in San Juan and Hatun puncha (great day), where the celebration calls the gratitude to the sun for the crops provided and the empowerment that makes visible the community, in addition, the sacred sites are preserved by the residents of the community site where the Armay tuta or ritual bath is performed. Thus, it was concluded that the Inti Raymi in the community of La Calera has had a certain transformation mainly in the clothing, likewise, the sacred site for the ritual bath was on the bridge of Yura Yaku (white river) at the entrance of the Otavalo canton, a tradition different from what it is today.